Effect of creative and reproductive dance sessions on high school students' physical activity, perceived exertion, and flow state - María del Mar Lara Aparicio; Iván López-Fernández; Daniel Mayorga-Vega (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Expressive Movement and Creative Dance is a discipline teaching in school Physical Education around the world that might benefit physical, psychological, social, and cognitive health. Nonetheless, the studies on the methodology to be followed are scarce. Thus, the purpose of this research was to compare high school students’ objective physical activity (ActiGraph GT3X+ accelerometer), perceived exertion (OMNI-walk/run Scale of Perceived Exertion), and flow state (Flow State Scale) between a creative and a reproductive dance session. Following a cluster-randomised crossover design, a total of 328 high school students (mean age = 14.0 ± 1.0; females, n = 172) participated in the study. Results showed that students experienced higher perceived exertion and were significantly more physically active during the creative session than during the reproductive one. For both sessions, flow state was equally high. Hence, although both dance sessions promoted flow state, the creative session best promoted high school students' physical activity engagement.